Study on the clogging mechanism of upward inclined drainage holes in cut slopes - Meng, Jian; Chen, An; Yin, Kexin; Zhou, Caihui (Frontiers in Earth Science, 2023)
Since groundwater is one of the main factors that affect the stability of highway slopes in mountainous regions, a smooth drainage is of importance for the safety of cut slopes. After years of service, the cut slopes of highway are often characterized with drainage problems or even drainage failures that threaten the stability and safety. In this paper, the clogging mechanism of drainage holes in highway cut slopes is firstly clarified through on-site survey. The soil and blockage samples are collected from typical slopes for laboratory tests and analysis, and the results reveal that all the blockages are made of fine-grained particles from the slopes. Scanning electron microscope (SEM) images indicate that the blockages penetrate the drainage pipe wrappings to form the clogging. The combined effect of clayey soil, chemicals, and biological clogging exacerbate the clogging process around the drainage pipes. Laboratory tests are also performed to simulate the CaCO3 crystal clogging around the drainage holes, and the microstructure of the clogged geotechnical screens and geotextiles is observed by scanning electron microscope as well. The results confirm that the amount of CaCO3 crystal attached to the drainage pipe surface increases with the time. The single-layer structure of screens does not facilitate the three-dimensional clogging as in the case of geotextiles. After soaking in diluted hydrochloric acid at a pH of 5.0, there is no significant decrease of CaCO3 crystals attached on the screens and geotextiles. However, the CaCO3 decrease is apparent after soaking in the hydrochloric acid at a pH of 3.0. The clogging of drainage holes can be classified into two stages according to the laboratory tests and acid soaking, and the relationship and characteristics between the two stages are summarized.